Strategies for Educational Service Marketing and Brand Equity Management in Educational Firms - Karimah, Yenny Dewi; Surachman, Surachman; Sunaryo, Sunaryo (International Journal Labs, 2023)
The term marketing is closely related to the world of profit trading business. However, it is different now since marketing terms are needed in various institutions, especially in educational institutions. Researchers studied marketing strategy and brand equity management, promotion mix strategy, marketing mix strategy, brand equity management, and the impact on institutions from implementing marketing strategy and brand equity management. at YPI Ar-Rohmah Putri Malang. This study uses a qualitative approach. This research phase is divided into three stages, namely the preparation stage, the implementation stage, and the completion stage. The researcher chose the research location at the Ar-Rohma Putri Islamic Education Foundation on Jl. Jambu, Semanding, Sumbersekar, Kec. Dau, Malang, East Java. Marketing strategy for marketing services through a promotional mix at the Islamic educational institution Ar-Rohmah Putri Islamic Boarding School Malang. The promotion mix is done through advertising, personal selling, sales promotion, public relations, word of mouth. Marketing strategy for marketing services through the marketing mix at the Islamic educational institution Ar-Rohmah Putri Islamic Boarding School Malang. The marketing mix for educational services includes product, price, location, promotion, people, physical evidence, and process.